2012
DOI: 10.1007/s00038-012-0360-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the use of healthcare services in children and adolescents in Spain

Abstract: No barriers to healthcare services use were found. Family level of education, family affluence and double healthcare coverage predicted the use of specialists and dentists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Our results on additional covariates are largely in concordance with findings from other prospective studies—showing that other health problems, measured as physical disease13 and mental health problems,14 predict increased healthcare use.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results on additional covariates are largely in concordance with findings from other prospective studies—showing that other health problems, measured as physical disease13 and mental health problems,14 predict increased healthcare use.…”
Section: Discussionsupporting
confidence: 90%
“…The psychometric properties of the Danish version have been evaluated29 and our data were interpreted using Danish norms 30. In accordance with previous practice,14 we dichotomised the score into ‘no’ and ‘yes’, where ‘yes’ consisted of children with ‘borderline’ and ‘abnormal’ total scores.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in the German research, it was found that families of higher SES used the primary care paediatrician services and those from the lower SES group used GP services (Rattay et al, 2014), while Wölfle et al (2014) described a higher use of somatic health care, but a lower use of mental health care in families of low SES compared to families with a higher SES, after adjusting the analysis for a mental health measure (SDQ). Two Spanish studies (Berra et al, 2006;Palacio-Vieira et al, 2013) reported generally equitable healthcare utilisation by children aged 5À14 years and 8À18 years, after adjusting for indicators of healthcare needs. In southern Sweden, Mangrio, Hansen, Lindstrom, Kohler, and Rosvall (2011) described a higher use of general practice in preschool children from families with low SES, compared to those with high SES and Ivert et al (2013) found a similar pattern in adolescent use of mental health care.…”
Section: Socio-economic Statusmentioning
confidence: 99%
“…The studies we found covered all ages of children. However, only four studies adjusted the analysis of healthcare utilisation to an indicator of healthcare need; these included the perceived health status in the use of primary care physicians in Spain (Berra et al, 2006), physical and mental health in Catalonia (Palacio-Vieira et al, 2013), morbidity load in Aragon, Spain (Calderon-Larrañaga et al, 2011), and a measure of mental health (SDQ) in use of somatic and mental health services in Germany (Wölfle et al, 2014).…”
Section: Healthcare Utilisation and Equity For Child Healthmentioning
confidence: 99%